Pošteno živeti, nikomur škodovati, vsakomur dati, kar mu gre - Prek, Miro (Pravnik, 2024)
The memory of professor, judge and the person of Marko Ilešič is being celebrated in the farewell speech. Marko Ilešič was born in 1947 and left us far too early in 2024, in his position of judge at the Court of Justice of the EU (CJEU): he was the first Slovenian judge at the CJEU and bid farewell on the twentieth anniversary of membership of Slovenia in the EU. Among the many excellent lawyers, judge Ilešič was probably the truest and most determined lover of the EU law: all his life, he was attracted to law, while the EU law became his late love which as any late love was even bigger and deeper. He devoted himself to the mission of the judge at the CJEU completely: his almost child-like unspoilt enthusiasm for problems he was called to solve in his (un)usual work as judge was breath-taking, commanded respect and was an immense inspiration for all those who had the privilege and honour to meet him. A description of his professional and life path is based on Ulpian’s legal precepts: iuris praecepta sunt haec: honeste vivere, alterum non laedere, suum cuique tribuere (in Latin “To live honestly, not to harm any other person, to render each his own”) that best summarise Marko’s attitude to work and life.
Keywords: Ilešič, Marko; nekrologi; pravniki; profesorji; Sodišče Evropske unije; sodniki; življenjepisi